ENHANCING TOURISM AWARENESS IN JAKARTA THROUGH ETHNO-WELLNESS SPAS UTILIZING BIG DATA ANALYTICS - Shanty Muni Parwati, Komang; Lanovia Amir, Firlie; Ayu Etsa Pracintya, Ida (Berajah Journal, 2024)
Various attractions, facilities, access, and community in a tourist destination are one of the tourist attractions that can be done. Another choice of tourist activities is the ethno-wellness spa which offers tourist activities by presenting ethnic uniqueness from every tribe in Indonesia in a spa nuance. The ethno-wellness spa is a tourist activity intended for tourists interested in having an experience of fitness tourism in the metropolitan city of Jakarta. This research aims to increase awareness of travel through ethno-wellness spas in metropolitan Jakarta. The type of research used in this study is qualitative descriptive, where data is taken and described qualitatively using Sugiono’s data triangulation analysis model in data processing. The instruments in this study used interview guides, documentation and collecting data from crowdsourcing. The participants in this study were spa therapists and visitors from five-star hotels in Jakarta. Visitors to five-star hotel spas in the metropolitan city of Jakarta began to know the existence of ethno-wellness spa activities as an alternative to other tourism through creative promotions from its stakeholders. This research contributes to stakeholders in ethno-wellness spa as a reference to maximize awareness of alternative travel activities in this field.